The The Role Of Hospital Information System (Sirs) On The Performance Of Medical Record Work Unit Services At Grandmed Lubuk Pakam Hospital on 2024 - Purba, Rini Armaida; samran; Bambang Sumantri (JURNAL KESMAS DAN GIZI (JKG), 2024)
Background: The rapid development of technology has changed various aspects of human life, including the health sector. Grandmed Lubuk Pakam Hospital utilizes the Hospital Information System (SIRS) to simplify information management and management in the hospital. Objectives: The research in this thesis aims to find out how the hospital information system (SIRS) affects the service performance of the media recording work unit at Grandmed Lubuk Pakam Hospital in 2024. Research method: The research method used is a qualitative approach with structured interviews and qualitative data analysis Results: The research results show that SRIS has an important role in improving the service performance of the medical records unit at Grandmed Lubuk Pakam Hospital. SRIS helps in collecting, recording, processing and analyzing medical record data which facilitates the medical service process. In this way, SRIS can increase the efficiency and effectiveness of media services, as well as improve the quality of services provided to patients. Conclusion: The conclusion of this research is that SIRS has a strategic role in improving the service performance of the medical records work unit at Grandmed Lubuk Pakam Hospital. Therefore, Grandmed Lubuk Pakam Hospital must continue to increase the use of SIRS to improve the quality of medical services provided to patients.